1976
DOI: 10.1021/bi00661a011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple acyl-coenzyme A carboxylases in Pseudomonas citronellolis

Abstract: Pseudomonas citronellolis was shown to contain four different acyl-coenzyme A carboxylases, including acetyl-, propionyl-, 3-methylcrotonyl-, and geranyl-CoA carboxylases, when grown on the appropriate carbon sources. Acetyl-CoA carboxylase activity in crude extracts was stimulated approximately 40-fold by inclusion of 0.4-0.5 M ammonium sulfate in the assay. Unexpectedly high levels of propionyl-CoA carboxylase activity, also stimulated by ammonium sulfate, were found in acetate-grown cells. That these acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…Carboxylation of 3-methylcrotonyl-CoA by biotin-dependent methylcrotonyl-CoA carboxylase yields 3-methylglutaconyl-CoA (50, 51), which is then transformed into three molecules of acetyl-CoA (4, 63). However, in contrast to other acyl-CoA esters, which are usually carboxylated at the ␣ position, the CO 2 group is in this case introduced at the ␥ position (50,52,59). Recently, the genes encoding geranoyl-CoA carboxylase, a homolog of 3-methylcrotonyl-CoA carboxylase, were identified and functionally assigned (4,63).…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
“…Carboxylation of 3-methylcrotonyl-CoA by biotin-dependent methylcrotonyl-CoA carboxylase yields 3-methylglutaconyl-CoA (50, 51), which is then transformed into three molecules of acetyl-CoA (4, 63). However, in contrast to other acyl-CoA esters, which are usually carboxylated at the ␣ position, the CO 2 group is in this case introduced at the ␥ position (50,52,59). Recently, the genes encoding geranoyl-CoA carboxylase, a homolog of 3-methylcrotonyl-CoA carboxylase, were identified and functionally assigned (4,63).…”
Section: Carboxylases In Assimilatory Pathwaysmentioning
confidence: 99%
“…The resulting metabolite (3-methylcrotonyl-CoA) is degraded via the leucine/isovalerate utilization (Liu) pathway (Fig. 1), which involves another carboxylase (methylcrotonyl-CoA carboxylase, MCase) that is unable to utilize geranyl-CoA as a substrate, but is able to utilize carboxylate methylcrotonylCoA (Fall & Hector, 1977;Fall, 1981;Hector & Fall, 1976a, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the P. citronellolis GCCase carboxylates both G-CoA and MC-CoA, while MCCase carboxylates only MC-CoA (9,13,15). Although the genes that encode the enzymes of the acyclic terpene and leucine/isovalerate catabolic pathways in P. aeruginosa and P. citronellolis have been recently elucidated (1,10), there is still uncertainty regarding the bifunctionality of the carboxylases involved.…”
mentioning
confidence: 99%